Sosialisasi Penggunaan Media Digital Yang Cerdas Bagi Pelajar di Desa Bandar Magodang - Mismahella, Igris; Wijaya, Aldy; Indah Riskiyah Harahap, Anggi; Dahlya Narpila, Suci (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this activity is to provide data to students about the intelligent use of digital media which can influence the turn of events and the use of science in the eyes of the public. This business is named